2016
DOI: 10.1111/sltb.12314
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Moderates the Association Between Perceived Burdensomeness and Suicide Ideation in Adults With Elevated Depressive Symptoms

Abstract: A conceptual model in which the associations between perceived burdensomeness and suicide ideation, and between thwarted belongingness and suicide ideation, are moderated by mindfulness was examined. Participants were 218 undergraduates (mean age = 20.81) with moderate-to-severe depressive symptoms. Mindfulness significantly moderated the association between perceived burdensomeness and suicide ideation; participants with thoughts of burdensomeness experienced lower levels of suicide ideation if they were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While IPTS theorizes that perceived burdensomeness and thwarted belonging are sufficient causes for a desire for death, a contextual behavioral science perspective would assert that these negative self-evaluations would only be seen as threatening to the extent that individuals experience them as “needs” for well-being at all, rather than difficult thoughts that one can respond to in many ways. Consistent with this prediction, flexible responses such as mindfulness ( Buitron, Hill, & Pettit, 2017 ; Collins, Best, Strizke, & Page, 2016 ) and pursuing personal values ( Bahraini et al, 2013 ) weaken the impacts of interpersonal need strain on task persistence or suicidal ideation. In contrast, thwarted belongingness demonstrates stronger links to suicidal ideation for those who value interpersonal relationships (i.e., who are failing that value; Monteith, Pease, Forster, Homaifar, & Bahraini, 2015 ).…”
Section: Introductionmentioning
confidence: 80%
“…While IPTS theorizes that perceived burdensomeness and thwarted belonging are sufficient causes for a desire for death, a contextual behavioral science perspective would assert that these negative self-evaluations would only be seen as threatening to the extent that individuals experience them as “needs” for well-being at all, rather than difficult thoughts that one can respond to in many ways. Consistent with this prediction, flexible responses such as mindfulness ( Buitron, Hill, & Pettit, 2017 ; Collins, Best, Strizke, & Page, 2016 ) and pursuing personal values ( Bahraini et al, 2013 ) weaken the impacts of interpersonal need strain on task persistence or suicidal ideation. In contrast, thwarted belongingness demonstrates stronger links to suicidal ideation for those who value interpersonal relationships (i.e., who are failing that value; Monteith, Pease, Forster, Homaifar, & Bahraini, 2015 ).…”
Section: Introductionmentioning
confidence: 80%
“…It is thus possible that suicide‐specific care which addresses how individuals are thinking may be more effective than treatments which address what individuals are thinking. Only a handful of studies have been conducted on ACT for treating individuals experiencing SI, but the few that have been conducted show preliminary evidence that ACT might be effective in reducing suicide risk (Buitron, Hill, & Pettit, ; Hayes, Pistorello, & Biglan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the search for meaning in life, viewed as a resilience factor, mediates the association between the IPTS variables and suicidal ideation (Kleiman & Beaver, 2013). Both self-forgiveness and mindfulness, also deemed to be resilience factors, have been found to moderate the relation between perceived burdensomeness and suicidal ideation (Buitron, Hill, & Pettit, in press; Cheavens, Cukrowicz, Hansen, & Mitchell, 2016). The current investigation expands upon this body of work by attending to suicide resilience as an outcome variable.…”
Section: Discussionmentioning
confidence: 99%